2017
DOI: 10.1053/j.ajkd.2016.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, Kidney Function, and Polypharmacy: The Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background Frail individuals are at increased risk for poor outcomes, including adverse drug events. Kidney function is often compromised in frailty and is a key consideration in medication choice and dosing; however, creatinine-based measures of kidney function may be biased in frail individuals. Study Design Observational study. Setting & Participants 4,987 community-dwelling older men and women with complete data who participated in visit 5 of the Atherosclerosis Risk in Communities (ARIC) Study (2011–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 47 publications
6
73
3
1
Order By: Relevance
“…Comparable to other reports, the prevalence of frailty increased with worsening kidney function in this cohort [5,38,39]. There was a similar age between non-frail and frail groups, highlighting that frailty is a syndrome that is not merely due to the ageing process.…”
Section: Discussioncontrasting
confidence: 49%
“…Comparable to other reports, the prevalence of frailty increased with worsening kidney function in this cohort [5,38,39]. There was a similar age between non-frail and frail groups, highlighting that frailty is a syndrome that is not merely due to the ageing process.…”
Section: Discussioncontrasting
confidence: 49%
“…The other potential factor that influencing on poor prognosis was frailty. Patients with CKD and CVD are more likely to be frail [22] because these are likely to exist in combination with comorbid conditions, disability, and polypharmacy [23,24]. In addition, frailty is also one of the important parameters of cancers [25,26].…”
Section: Risk-score-based Protocol Months After Rcmentioning
confidence: 99%
“…A study by Roshanravan et al found that the relationship between frailty and CKD was attenuated when using creatinine instead of Cystatin C to estimate GFR (28). This was supported by a more recent retrospective analysis by Ballew et al of 4987 community dwellers comparing cystatin C and creatinine clearance and the relationship with frailty (42). In five studies, there was significant increase in the risk of frailty with eGFR less than 45mLs per minute (16,(27)(28)(29)(30).…”
Section: Glomerular Filtration Rate and Frailtymentioning
confidence: 84%
“…23,25,26,29- 33 Frailty also predicted an increased risk of falls in patients with CKD. 34,42 In the kidney transplant recipient, frailty was associated with an increased risk of early hospital readmission and delayed graft function. 35,36 Patients who were frail prior to transplantation were also more likely to have improvement in frailty after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation